Water-blocking and anti-falling cement mortar-putty powder coating structure and preparation method thereof
By adding stearic acid powder and cotton fibers to the cement mortar to form a water-repellent cement mortar layer and a water-repellent putty powder layer, the problems of poor waterproofness, insufficient crack resistance and easy shedding of traditional cement mortar are solved, and more efficient waterproof, crack resistance and shedding resistance are achieved.
Patent Information
- Application Number
- CN202510079976.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing cement mortar has shortcomings in waterproof, crack resistance and shed resistance. Especially in humid environments or changes in temperature and humidity, the waterproof effect is prone to deterioration, and the coating is prone to cracks or fall off.
A multi-layer structure of a water-repellent cement mortar layer and a water-repellent putty powder layer is adopted to form a hydrophobic film by heating the stearic acid powder and sand, which enhances the water repellency of the sand particles, and spreads cotton fibers on the surface of the cement mortar to enhance crack resistance and shed resistance.
It significantly improves the waterproof performance of cement mortar, enhances crack resistance and shed resistance, and forms a more durable and stable coating structure, suitable for building surfaces that are exposed to humid environments for a long time.
Smart Images

Figure CN119899552A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a water-blocking and anti-shedding cement mortar-putty powder coating structure and a preparation method thereof. Background Art
[0002] In construction projects, cement mortar, as a common wall coating material, is widely used in the protection and decoration of buildings. However, existing cement mortar has certain deficiencies in terms of waterproof, crack resistance and anti-shedding performance. Especially when exposed to a humid environment for a long time or encountering temperature and humidity changes, the waterproof effect of traditional cement mortar is prone to degradation, and the coating is prone to cracks, shedding and other problems when subjected to external force impact or temperature changes. The structure of traditional cement mortar is relatively simple, and it mainly relies on the hardening effect of cement to form a coating, which makes it limited in its protection ability when facing environmental factors such as moisture penetration and temperature changes.
[0003] In order to solve these problems, many studies have proposed to improve the performance of cement mortar by adding different additives or materials. For example, by introducing modifiers and anti-cracking fibers into cement mortar, the crack resistance and toughness of cement mortar can be enhanced to a certain extent. However, these improvements are mostly focused on optimizing a single aspect, such as enhancing crack resistance and improving permeability resistance, but it is difficult to take into account multiple aspects of performance in one coating at the same time. For example, although some technologies can improve the waterproofness of cement mortar, they usually sacrifice its crack resistance or anti-falling properties, resulting in instability of the coating during long-term use, especially in environments with large temperature differences or high humidity, where the cement mortar layer is prone to cracking or falling off.
[0004] In addition, although the existing anti-water penetration technology uses different waterproof additives and structural designs, such as stearates, polymers and other materials, these methods usually only focus on the waterproof effect and ignore the overall stability and durability of the coating. For the application of cotton fiber, although studies have shown that it has certain advantages in preventing the putty powder layer from falling off in blocks, it has not yet formed a multifunctional coating structure that can simultaneously improve waterproofness, crack resistance, and fall-off resistance. Most technical solutions in the existing technology are difficult to effectively integrate materials with different functions, which makes it unable to meet the needs of long-term use in practical applications.
[0005] Therefore, the present invention proposes a water-blocking and anti-shedding cement mortar-putty powder coating structure and a preparation method to solve the deficiencies of the prior art. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a water-resistant and anti-shedding cement mortar-putty powder coating structure and a preparation method, which solves the problems of traditional cement mortar coatings in terms of poor waterproofness, insufficient crack resistance and easy shedding of the coating.
[0007] To achieve the above purpose, the present invention is implemented by the following technical scheme: a water-blocking and anti-shedding cement mortar-putty powder coating structure and preparation method, comprising the following components:
[0008] The water-repellent cement mortar layer is made of the following components in proportion by mass:
[0009] Sand: 60%~80%;
[0010] Stearic acid powder: 0.1%~0.3%;
[0011] Cement: 15% to 30%;
[0012] Water: 10%-15%;
[0013] When stearic acid powder and sand are heated, a hydrophobic film forms on the surface of the sand, greatly reducing the possibility of water penetration. The stearic acid molecules form non-polar interactions with the surface in the cement mortar through their long-chain hydrocarbon groups, thereby enhancing the water repellency of the sand. In this way, the sand itself becomes extremely hydrophobic, further improving the waterproof performance of the cement mortar.
[0014] At the same time, the hydrophobic properties of cement mortar are also related to the curing process of cement. The hydrate in cement and stearic acid powder work together to further enhance the waterproof ability of cement mortar, reduce water penetration, and enhance the overall durability of the mortar layer.
[0015] The water-repellent putty powder layer is prepared by mixing the following components in proportion by mass:
[0016] Putty powder: 85%~95%;
[0017] Stearic acid powder: 1% to 3%;
[0018] Cotton fiber: 0.1%~0.2%.
[0019] Preferably, the mixture of sand and stearic acid powder in the water-repellent cement mortar layer is prepared by heating at a temperature of 95° C. to 105° C. for 2 to 4 hours, and stirring is performed every 30 minutes during the heating process.
[0020] Preferably, the cotton fibers in the water-repellent cement mortar layer are natural cotton fibers, which are treated with a dispersant and cut to a length of less than 1 cm.
[0021] Preferably, the mixing ratio of the water-repellent cement mortar layer is water-repellent sand:cement=2:1 to 3:1, cement:water=1:0.3 to 1:0.5.
[0022] Preferably, when cotton fibers are spread on the surface of the cement mortar layer, the spreading amount of the cotton fibers is 0.1% to 0.3%.
[0023] The present invention also provides a method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure, comprising the following steps:
[0024] S1. Preparation of water-repellent cement mortar layer:
[0025] S2. Spread cotton fibers on the surface of cement mortar:
[0026] S3. Prepare a water-repellent putty powder layer, add cotton fiber, and apply it on the surface of cement mortar:
[0027] S4. Wait for the cement mortar layer to solidify at room temperature.
[0028] Preferably, the cement mortar layer is formed by mixing water-repellent sand, cement and clean water in a certain proportion and stirring them evenly to form a water-repellent cement mortar layer.
[0029] Preferably, the water-repellent putty powder layer is prepared by mixing putty powder and stearic acid powder in a mass ratio of 2%, and heating and stirring.
[0030] Preferably, the cotton fibers are treated with a dispersant and cut to a length of less than 1 cm.
[0031] Preferably, the heating time is 2 to 4 hours, and stirring is performed every 30 minutes.
[0032] The present invention provides a water-blocking and anti-shedding cement mortar-putty powder coating structure and a preparation method thereof. It has the following beneficial effects:
[0033] 1. The present invention adopts a technical solution of combining water-repellent cement mortar with stearic acid powder, and forms a strong hydrophobic layer on the surface of sand particles through heating treatment, thereby achieving the technical effect of effectively preventing water penetration. Compared with the technical solution of the prior art that only relies on conventional cement mortar, the problem of poor waterproofness is solved, and the water penetration resistance of cement mortar is significantly improved.
[0034] 2. The present invention spreads cotton fibers treated with a dispersant on the surface of cement mortar, so that the crack resistance and anti-falling property of cement mortar are enhanced during the curing process, thereby achieving the technical effect of improving the toughness of the mortar structure. Compared with the mortar solution that does not consider fiber reinforcement in the prior art, the defects of easy cracking and falling off are solved, and the long-term stability of the coating is increased.
[0035] 3. By using the composite technology of water-repellent putty powder and stearic acid powder, the putty powder layer is ensured to have good waterproof performance, achieving the technical effect of enhancing the waterproof effect of the overall coating. Compared with the technical solution of relying only on a single putty powder coating in the prior art, the problem that the putty powder layer is easily ineffective due to moisture intrusion is solved, providing more lasting protection.
[0036] 4. By combining the water-repellent cement mortar layer, the cotton fiber layer and the water-repellent putty powder layer, a multi-layer protective structure is formed, achieving the technical effect of overall enhanced waterproofness and anti-shedding properties of the coating. Compared with the technical solution of only using a single waterproof or enhancement method in the prior art, it solves the problem of single structure and limited effect, and improves the comprehensive performance of the coating under different environmental conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a flow chart for preparing the cement mortar-putty powder coating structure;
[0038] Figure 2 This is a schematic diagram of the structure of applying cement mortar to the wall surface of the present invention;
[0039] Figure 3 The present invention is a structural schematic diagram of a cement mortar-putty powder coating applied to a wall surface. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Please refer to the attached Figure 1 - Attachment Figure 3
[0042] Embodiment 1:
[0043] Materials preparation:
[0044] Ratio of sand to stearic acid powder: 0.2%;
[0045] Heating temperature: 100℃;
[0046] Heating time: 2 hours;
[0047] Cement to water ratio: 1:0.4;
[0048] Cotton fiber spreading amount: 0.2%;
[0049] Preparation steps:
[0050] Mix 60 parts of sand with 0.2 parts of stearic acid powder, put it in an oven, set the temperature to 100°C, and heat it for 2 hours. Stir it every 30 minutes to ensure that the stearic acid powder is evenly distributed on the surface of the sand.
[0051] After the heated sand is cooled to room temperature, it is mixed with 30 parts of cement and 12 parts of water and stirred evenly to obtain water-repellent cement mortar.
[0052] Apply the prepared cement mortar to the foundation wall and level the surface.
[0053] Spread cotton fibers treated with dispersants and cut to less than 1 cm evenly on the surface of cement mortar, ensuring that the fibers do not clump and are evenly distributed.
[0054] Allow the cement mortar to cure naturally for more than 24 hours to complete the waterproofing and strengthening of the coating.
[0055] Embodiment 2:
[0056] Materials preparation:
[0057] Ratio of sand to stearic acid powder: 0.15%;
[0058] Heating temperature: 95°C;
[0059] Heating time: 2 hours;
[0060] Cement to water ratio: 1:0.3;
[0061] Cotton fiber spreading amount: 0.1%;
[0062] Preparation steps:
[0063] Mix 70 parts of sand with 0.15 parts of stearic acid powder and heat in an oven at 95°C for 2 hours. Stir every 30 minutes to ensure uniform processing.
[0064] The heated sand is mixed with 35 parts of cement, and 10.5 parts of water are added and stirred evenly to form a dense water-repellent cement mortar.
[0065] Apply cement mortar to the exterior wall surface, ensuring the coating is smooth and even.
[0066] Spread cotton fibers cut to 1 cm in length, and control the spreading amount to 0.1% to ensure that each area is evenly covered.
[0067] Allow the coating to cure naturally for 24 hours to form a strong, waterproof finish.
[0068] Embodiment 3:
[0069] Materials preparation:
[0070] Ratio of sand to stearic acid powder: 0.3%;
[0071] Heating temperature: 105°C;
[0072] Heating time: 3 hours;
[0073] Cement to water ratio: 1:0.5;
[0074] Cotton fiber spreading amount: 0.25%;
[0075] Preparation steps:
[0076] Mix 75 parts of sand with 0.3 parts of stearic acid powder according to the weight ratio and heat in an oven. The heating temperature is 105°C for 3 hours, stirring every 30 minutes to ensure that the stearic acid powder is evenly coated on the sand.
[0077] The cooled sand is mixed with 35 parts of cement, and 17.5 parts of water are added and stirred until a uniform water-repellent cement mortar is formed.
[0078] Apply cement mortar to the basement walls, ensuring an even thickness and smooth surface.
[0079] Spread the treated cotton fibers, cut to less than 1 cm, at a spreading rate of 0.25%, ensuring that there is no clumping and the fibers are evenly distributed.
[0080] Wait for the coating to cure at room temperature for more than 48 hours to ensure that the coating is fully cured and has good waterproof properties.
[0081] Embodiment 4:
[0082] Materials preparation:
[0083] Ratio of sand to stearic acid powder: 0.2%;
[0084] Heating temperature: 100℃;
[0085] Heating time: 2.5 hours;
[0086] Cement to water ratio: 1:0.4;
[0087] Cotton fiber spreading amount: 0.15%;
[0088] Preparation steps:
[0089] 65 parts of sand were mixed with 0.2 parts of stearic acid powder and placed in an oven and heated to 100°C for 2.5 hours, stirring every 30 minutes to ensure that the stearic acid evenly covered the sand particles.
[0090] The treated sand was mixed with 30 parts of cement and 12 parts of water, and stirred evenly to obtain a water-repellent cement mortar.
[0091] Apply cement mortar evenly on the balcony surface, level the surface and ensure even coating.
[0092] The treated cotton fibers were spread evenly, with the length controlled within 1 cm and the spreading amount being 0.15%.
[0093] Allow the coating to cure for 24 hours to ensure it is fully waterproof.
[0094] Comparative Example:
[0095] Comparative Example 1:
[0096] Materials preparation:
[0097] Ratio of sand to stearic acid powder: no stearic acid powder added;
[0098] Heating temperature: normal temperature treatment;
[0099] Heating time: No heating treatment;
[0100] Cement to water ratio: 1:0.4;
[0101] Cotton fiber spreading amount: no cotton fiber added;
[0102] Preparation steps:
[0103] 75 parts of sand were mixed directly with 30 parts of cement without adding stearic acid powder.
[0104] Add 12 parts of water and mix well to form regular cement mortar.
[0105] Apply the mixed cement mortar evenly on the foundation wall and level the surface.
[0106] No additional fiber material processing or addition.
[0107] Comparative Example 2:
[0108] Materials preparation:
[0109] Ratio of sand to stearic acid powder: 0.2%;
[0110] Heating temperature: 100℃;
[0111] Heating time: 2 hours;
[0112] Cement to water ratio: 1:0.4;
[0113] Cotton fiber spreading amount: no cotton fiber added;
[0114] Preparation steps:
[0115] Mix 60 parts of sand with 0.2 parts of stearic acid powder, put into an oven, set the temperature to 100°C, and heat for 2 hours. Stir every 30 minutes.
[0116] The cooled sand is mixed with 30 parts of cement and 12 parts of water, and stirred evenly to obtain a water-repellent cement mortar.
[0117] Apply cement mortar evenly on the wall and level the surface.
[0118] No fiber materials are added.
[0119] Comparative Example 3:
[0120] Materials preparation:
[0121] Ratio of sand to stearic acid powder: no stearic acid powder;
[0122] Heating temperature: normal temperature treatment;
[0123] Heating time: No heating treatment;
[0124] Cement to water ratio: 1:0.4;
[0125] Cotton fiber spreading amount: 0.2%;
[0126] Preparation steps:
[0127] 70 parts of sand were mixed with 30 parts of cement without adding stearic acid powder.
[0128] Add 12 parts of water and stir evenly to obtain conventional cement mortar.
[0129] Spread 0.2% cotton fibers on the surface of cement mortar, ensuring that the fibers are evenly distributed.
[0130] Apply the mixed mortar to the wall and level the surface.
[0131] Allow the cement mortar layer to cure naturally for 24 hours.
[0132] Comparative Example 4:
[0133] Materials preparation:
[0134] Ratio of sand to stearic acid powder: 0.2%;
[0135] Heating temperature: 100℃;
[0136] Heating time: 2 hours;
[0137] Cement to water ratio: 1:0.4;
[0138] Cotton fiber spreading amount: 0.1%;
[0139] Putty powder: Traditional putty powder without water-repellent ingredients
[0140] Preparation steps:
[0141] Mix 60 parts of sand with 0.2 parts of stearic acid powder, put into an oven, set the temperature to 100°C, heat for 2 hours, and stir every 30 minutes.
[0142] The treated sand is mixed with 30 parts cement and 12 parts water to form a water-repellent cement mortar.
[0143] Spread 0.1% cotton fiber evenly on the surface of cement mortar.
[0144] Use traditional putty powder without water-repellent ingredients to apply it on the mortar surface without heating the putty powder.
[0145] Curing treatment: wait for the coating to cure naturally for more than 24 hours.
[0146] Comparative Example 5: Using water-repellent cement mortar and conventional putty powder (without cotton fiber)
[0147] Materials preparation:
[0148] Ratio of sand to stearic acid powder: 0.2%;
[0149] Heating temperature: 100℃;
[0150] Heating time: 2 hours;
[0151] Cement to water ratio: 1:0.4;
[0152] Cotton fiber spreading amount: no cotton fiber added;
[0153] Putty powder: putty powder without water-repellent ingredients;
[0154] Preparation steps:
[0155] Mix 60 parts of sand with 0.2 parts of stearic acid powder, put into an oven, set the temperature to 100°C, heat for 2 hours, and stir every 30 minutes.
[0156] The sand was mixed with 30 parts of cement and 12 parts of water to obtain a water-repellent cement mortar.
[0157] Apply a layer of conventional putty powder without added water-repellent ingredients on the surface of the cement mortar.
[0158] After curing treatment, the cement mortar surface is naturally cured for 24 hours.
[0159] Test experiment
[0160] Experiment 1: Waterproof performance test
[0161] Experimental steps:
[0162] Two groups of test pieces were prepared, namely, Example 1 and Comparative Example 1;
[0163] The coating of Example 1 is composed of water-repellent cement mortar;
[0164] Comparative Example 1 is a traditional cement mortar without adding stearic acid powder or cotton fiber.
[0165] To ensure that the coating thickness of each sample is consistent, cement mortar is applied to the surface of the specimen and the surface is smoothed using a scraper to ensure that the coating thickness is approximately the same.
[0166] The coating samples were cured at room temperature for 24 hours.
[0167] The cured specimens were subjected to water penetration test. Each specimen was placed in a standard water penetration test device, and an isobaric water flow was applied to its surface, with the pressure set to 0.2 MPa.
[0168] The test lasted for 48 hours, and the amount of water penetration was recorded every 6 hours until traces of water penetration appeared on the surface of the specimen.
[0169] Experimental data record:
[0170] Water penetration test data comparison table
[0171]
[0172] Experimental summary:
[0173] The experimental results clearly show that the water-repellent cement mortar and cotton fiber composite coating in Example 1 has obvious advantages in waterproof performance. Compared with Comparative Example 1, the water permeation of Example 1 is significantly lower than that of Comparative Example 1, indicating that the combined use of stearic acid powder and cotton fiber effectively improves the waterproof performance. Especially in the first few hours of the permeation experiment, Example 1 shows extremely low water permeation. This phenomenon reflects that the hydrophobic film formed by stearic acid powder on the surface of sand particles effectively prevents the penetration of water, thereby greatly enhancing the waterproofness of the cement mortar layer.
[0174] Further analysis and experimental results also proved the reinforcing effect of cotton fibers. Although the addition of stearic acid powder itself provides basic waterproofing function, the addition of cotton fibers brings an additional effect, enhancing the overall structural stability of the coating and avoiding the expansion of microcracks during water penetration. The effect of this fiber network significantly reduces the passage of water through the coating, thereby achieving a more lasting waterproof effect.
[0175] Overall, the water-repellent cement mortar and cotton fiber combination technology of the present invention can significantly improve the waterproofness of cement mortar. Mechanistically, the hydrophobic effect of stearic acid and the reinforced structure of the fiber complement each other to form a more complete waterproof barrier. This innovative combination not only solves the problem of insufficient waterproofness of cement mortar in the prior art, but also significantly improves its long-term durability in humid environments.
[0176] Experiment 2: Crack resistance test
[0177] Experimental steps:
[0178] Two groups of test pieces were prepared, namely Example 2 and Comparative Example 3. The coating of Example 2 consisted of water-repellent cement mortar and cotton fiber, while Comparative Example 3 used conventional cement mortar and added cotton fiber.
[0179] Prepare concrete specimens of the same size (size: 10 cm×10 cm×2 cm) to ensure that the required coating is evenly coated on the surface of each specimen.
[0180] After curing for 72 hours, the specimens were exposed to an alternating temperature and humidity environment to simulate freeze-thaw cycle conditions. Each specimen was subjected to 30 freeze-thaw cycles (temperature range: ~5°C to 50°C), each freeze-thaw cycle lasting 24 hours. After every 10 freeze-thaw cycles, the specimen surface was checked for cracks, and the number, length, and width of the cracks were recorded.
[0181] The crack resistance of the coating can be evaluated by observing and recording the changes in the cracks.
[0182] Experimental data record:
[0183] Crack resistance test data comparison table
[0184]
[0185] Experimental summary:
[0186] The experimental results show that the crack resistance of Example 2 (water-repellent cement mortar + cotton fiber) is significantly better than that of Comparative Example 3 (ordinary cement mortar + cotton fiber). Especially after freeze-thaw cycles, the number and width of cracks in the coating of Example 2 are much lower than those in Comparative Example 3. The key to achieving this effect lies in the structural effect of cotton fibers. Cotton fibers form a stable physical network structure in cement mortar, which plays a bridging role during the freeze-thaw process and reduces the expansion of microcracks. This enhancement effect is not provided by Comparative Example 3, which cannot effectively prevent the generation of cracks caused by temperature changes by simply adding conventional cement mortar and fibers.
[0187] The role of stearic acid powder in Example 2 cannot be ignored. It enhances the hydrophobicity of the mortar, making the cement mortar surface more resistant to moisture, avoiding the expansion and contraction of water during the freezing and thawing process, thereby reducing the probability of cracks. Combined with the interaction of these components, the coating maintains good structural stability in an alternating hot and cold environment.
[0188] In summary, this experiment not only demonstrates the superiority of the solution of the present invention, but also reveals how the combination of water repellency and fiber reinforcement can provide stronger crack resistance in cold and humid environments. This improvement provides a new solution for the long-term durability of building materials, avoiding the shortcomings of poor crack resistance in the prior art.
[0189] Experiment 3: Anti-fall test
[0190] Experimental steps:
[0191] Two groups of test pieces were prepared, namely Example 4 and Comparative Example 4. Example 4 used water-repellent cement mortar combined with cotton fiber and water-repellent putty powder, while Comparative Example 4 used water-repellent cement mortar and traditional putty powder.
[0192] Prepare concrete specimens of the same size (size: 20cm×20cm×1cm). Apply different coatings evenly on the surface of each specimen to ensure consistent thickness.
[0193] After curing for 72 hours, the specimens were placed in an artificial simulated environment. A fixed load (15 kg) was applied to each sample, and pressure was applied in the vertical direction.
[0194] External force is applied every 10 minutes for 1 hour to simulate the external force that the coating will encounter during long-term use.
[0195] Record whether the surface of each specimen has fallen off or been severely damaged, and evaluate the coating's anti-falling property.
[0196] Experimental data record:
[0197] Anti-shedding test data comparison table
[0198]
[0199] Experimental summary:
[0200] The experimental results clearly show the obvious advantages of the coating of Example 4 in terms of anti-shedding. By combining water-repellent cement mortar, cotton fiber and water-repellent putty powder, Example 4 not only improves the waterproofness of the coating, but also enhances the adhesion of the coating. Compared with Comparative Example 4, the coating of Example 4 shows a strong ability to resist external force damage, and the shedding area and number of layers are significantly lower than those of Comparative Example 4. This shows that the addition of fibers provides a stable network structure at the physical level, so that the coating can effectively disperse stress under the action of external force, reducing the occurrence of cracks and shedding.
[0201] From a mechanism perspective, the hydrophobic effect of stearic acid powder combined with the reinforcing effect of cotton fiber forms a coating structure with dual protection. The hydrophobic film formed by stearic acid powder on the mortar surface effectively prevents water penetration and avoids the destructive effect of water on the coating, while cotton fiber improves the toughness of the coating, making it more evenly disperse the stress when it is subjected to force, reducing the risk of cracking and falling off of the coating.
[0202] Therefore, in general, the combination of water-repellent cement mortar, cotton fiber and water-repellent putty powder not only solves the waterproof problem in the existing technology from the perspective of waterproof performance, but also provides significant advantages in terms of crack resistance, anti-falling resistance, etc. With the in-depth study of material properties, further optimization of the proportion and combination of these composite materials will help to achieve a more durable and stable building coating solution.
[0203] Experiment 4: Comprehensive performance evaluation test
[0204] Experimental steps:
[0205] Two groups of test pieces were prepared, namely Example 3 and Comparative Example 5.
[0206] Example 3 adopts a three-layer structure of water-repellent cement mortar, cotton fiber and water-repellent putty powder, the ratio of cement to water is 1:0.4, and the cotton fiber spreading amount is 0.2%;
[0207] Comparative Example 5 uses water-repellent cement mortar and conventional putty powder, cotton fiber spreading amount: no cotton fiber is added, putty powder: putty powder without adding water-repellent ingredients.
[0208] Concrete specimens of the same size (dimensions: 20 cm × 20 cm × 2 cm) were prepared to ensure that the coating thickness of each specimen was consistent and were treated according to different coating schemes.
[0209] After curing for 72 hours, the specimens were placed in a standard test environment and subjected to a series of comprehensive performance tests, including:
[0210] Water penetration test: Use standard water penetration equipment, apply isobaric water flow (pressure 0.2MPa), and record the amount of water penetration within 48 hours.
[0211] Crack resistance test: Perform 30 freeze-thaw cycles (temperature range: -5°C to 50°C), check the crack development every 10 times, and record the number and size of cracks.
[0212] Anti-shedding test: Apply a fixed load of 15kg, apply external force vertically downward for 1 hour, and record the shedding area and number of layers of the coating.
[0213] After each test, the data is recorded and the comprehensive performance of different specimens is evaluated.
[0214] Experimental data record:
[0215] Comprehensive performance evaluation data comparison table
[0216]
[0217]
[0218] Experimental summary:
[0219] The experimental results show that the coating of Example 3 exhibits significant superiority in water permeability, crack resistance and anti-falling resistance. Compared with Comparative Example 5, the various performance indicators of Example 3 are significantly better than those of the traditional coating, especially in terms of water penetration, Example 3 performs better, with almost no water penetration. This shows that the composite coating of water-repellent cement mortar combined with cotton fiber can effectively prevent water penetration, improve waterproofness, and maintain stability under extreme environments.
[0220] From the perspective of mechanism analysis, stearic acid powder reduces the possibility of water penetration by enhancing the hydrophobicity of the mortar, while cotton fiber significantly reduces the generation of cracks during freeze-thaw cycles by enhancing the structural stability of the coating. Cotton fiber forms a support network in the coating, making it less likely for the coating to crack or fall off when it encounters freeze-thaw expansion and contraction. The combined effect enables the coating to maintain better structural stability when subjected to external forces or extreme climatic conditions.
[0221] The test results of comprehensive performance further show that the composite coating technology of Example 3 has longer durability and resistance to external forces. The addition of cotton fiber not only improves the crack resistance and the resistance to falling off, but also works together with the water-repellent cement mortar to form a more solid and durable protective layer. Therefore, the scheme of the present invention effectively overcomes the problems of poor waterproof performance, insufficient crack resistance and easy falling off of traditional cement mortar through the synergistic effect of physical structure and chemical composition, and provides a more reliable and durable building coating solution.
[0222] Please refer to the attached Figure 1The present invention also provides a method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure, comprising the following steps:
[0223] S1. Preparation of water-repellent cement mortar layer:
[0224] S2. Spread cotton fibers on the surface of cement mortar:
[0225] S3. Prepare a water-repellent putty powder layer, add cotton fiber, and apply it on the surface of cement mortar:
[0226] S4. Wait for the cement mortar layer to solidify at room temperature.
[0227] First, when preparing the water-repellent cement mortar layer, sand, stearic acid powder, cement and water are selected as raw materials. Stearic acid powder is fully combined with sand by heating to form a hydrophobic film, which significantly enhances the water resistance of the sand particles. After the mixture of sand and stearic acid powder is heated, it is cooled to room temperature, mixed with cement and water in a specific proportion, and stirred evenly to form a water-repellent cement mortar layer with extremely strong water resistance. The improvement of this layer of water resistance is mainly attributed to the hydrophobic effect of stearic acid powder, which prevents water from penetrating into the cement mortar, solving the problem of poor water resistance of traditional cement mortar.
[0228] When cotton fibers are spread on the surface of cement mortar layer, the dispersed cotton fibers are evenly spread on the surface of cement mortar, and the length of the fibers is usually controlled below 1 cm. The addition of fibers enhances the crack resistance and anti-falling property of cement mortar layer, ensuring that the coating is not easy to crack or fall off under stress. The combination of cotton fibers and cement mortar forms a stable physical network, which can effectively prevent the expansion of micro cracks and improve the toughness of the overall structure.
[0229] Next, when preparing the water-repellent putty powder layer, the putty powder and stearic acid powder are mixed in proportion and then heated to form a hydrophobic putty powder. The heated putty powder and the treated cotton fiber are further stirred evenly and then applied to the prepared cement mortar surface. The application of the putty powder layer further improves the waterproof effect and forms a second waterproof barrier. At the same time, the fiber enhances the adhesion of the putty powder layer, making it difficult to fall off. This step ensures the overall stability and durability of the coating, especially plays an important role in waterproofing and crack resistance.
[0230] Finally, the cement mortar layer is cured at room temperature to ensure a stable bond between the coatings. The curing process is the key to ensuring the performance of the coating. The cured coating will show extremely strong adhesion and water penetration resistance, and the ability to resist external damage is also significantly improved. Through this series of treatments, the present invention provides a high-efficiency coating structure with long-term waterproof, crack-resistant and anti-shedding properties, which overcomes the shortcomings of poor waterproofness and coating shedding in traditional technologies, and is suitable for building surfaces that are exposed to humid environments for a long time.
[0231] In summary, the present invention provides a water-blocking and anti-shedding cement mortar-putty powder coating structure, which significantly improves the waterproofness, crack resistance and anti-shedding properties of the coating through the organic combination of water-repellent cement mortar, cotton fiber layer and water-repellent putty powder layer. Stearic acid powder gives the cement mortar extremely strong hydrophobicity, cotton fiber enhances the toughness of the coating to prevent cracking and shedding, and the water-repellent putty powder layer further improves the waterproof performance and adhesion. Through this multi-layer composite structure, the present invention solves the problems of poor waterproofness of cement mortar and easy shedding of the coating in the prior art, and provides an efficient and durable coating solution, which is particularly suitable for the exterior surface of buildings that need to withstand moisture and external force damage for a long time.
[0232] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A water-blocking and anti-shedding cement mortar-putty powder coating structure, characterized in that: It includes the following components: The water-repellent cement mortar layer is made of the following components in proportion by mass: Sand: 60%~80%; Stearic acid powder: 0.1%~0.3%; Cement: 15% to 30%; Water: 10%-15%; The water-repellent putty powder layer is prepared by mixing the following components in proportion by mass: Putty powder: 85%~95%; Stearic acid powder: 1% to 3%; Cotton fiber: 0.1%~0.2%.
2. A water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 1, characterized in that: The mixture of sand and stearic acid powder in the water-repellent cement mortar layer is prepared by heating at a temperature of 95° C. to 105° C. for 2 to 4 hours, and the mixture is stirred every 30 minutes during the heating process.
3. A water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 1, characterized in that: The cotton fibers in the water-repellent cement mortar layer are natural cotton fibers that are treated with a dispersant and cut to less than 1 cm.
4. A water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 1, characterized in that: The mixing ratio of the water-repellent cement mortar layer is water-repellent sand:cement=2:1 to 3:1, cement:water=1:0.3 to 1:0.
5.
5. The water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 1 is characterized in that: When cotton fibers are spread on the surface of the cement mortar layer, the spreading amount of the cotton fibers is 0.1% to 0.3%.
6. The method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 1, characterized in that: The following steps are involved: S1. Preparation of water-repellent cement mortar layer: S2. Spread cotton fibers on the surface of cement mortar: S3. Prepare a water-repellent putty powder layer, add cotton fiber, and apply it on the surface of cement mortar: S4. Wait for the cement mortar layer to solidify at room temperature.
7. The method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 6, characterized in that: The cement mortar layer is formed by mixing water-repellent sand, cement and clean water according to a proportion and stirring them evenly to form a water-repellent cement mortar layer.
8. The method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 6, characterized in that: The water-repellent putty powder layer is prepared by mixing putty powder and stearic acid powder in a mass ratio of 2%, and heating and stirring.
9. The method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 6, characterized in that: The cotton fibers are treated with a dispersant and cut to a length of less than 1 cm.
10. The method for preparing a water-blocking and anti-shedding cement mortar-putty powder coating structure according to claim 8, characterized in that: The heating time is 2 to 4 hours, and the mixture is stirred every 30 minutes.